Cytotoxic effect of aminoglycoside antibiotics on the mammalian cell lines. Issue 1 (9th October 2020) - Kovacik, Anton; Tvrda, Eva; Jambor, Tomas; Fulopova, Diana; Kovacikova, Eva; Hleba, Lukas; Kołodziejczyk, Łukasz M.; Hlebova, Miroslava; Gren, Agnieszka; Massanyi, Peter
Abstract: Aminoglycoside antibiotics have been used for treating serious but also routine infections in veterinary and human medicine for many years. The basic aim of this work is to evaluate the cytotoxicity of dihydrostreptomycin and neomycin in vitro on three cell cultures - BHK-21 (Syrian golden hamster kidney fibroblast), VERO (African green monkey kidney fibroblast) and FEA (feline embryonic fibroblast) cells. The morphological changes were examined by Giemsa staining. Cells were dried and visualized under fluorescence microscope. After the exposure to different experimental doses of dihydrostreptomycin (812.5-20000 µg/mL) and neomycin (1000-20000 µg/mL) during 24 h, the viability of BHK-21, FEA and VERO cell lines were evaluated by MTT assay. Viability of BHK-21 cells significantly (P < 0.001) decreased after treatment with 3500; 5500 and 7500 µg/mL of dihydrostreptomycin and 9000; 10000 and 20000 µg/mL of neomycin. The FEA cell viability decreased significantly (P < 0.001; P < 0.01) at 2500 and 3000 µg/mL dihydrostreptomycin and at 3000 µg/mL of neomycin treatment. Only the highest concentration of dihydrostreptomycin (20000 µg/mL) reduced VERO cell viability significantly (P < 0.01). Based on or results we can assume the effect of different antibiotics in different concentrations on cell lines is various. Detection of antibiotic toxicity to animal cells is very important because of the increasing resistance of bacteria. One of the solutions is drug dose increasing, but only to a certain concentration, since the toxic effect over the therapeutic one will prevail, which we have also shown in this work.